2006
DOI: 10.1007/s00595-006-3226-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hypoxemia After Surgery for Acute Type A Aortic Dissection

Abstract: Initiating early treatment for hypoxemia and reducing the volume of blood transfused intraoperatively may improve the postoperative clinical course of obese patients with preoperative hypoxemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
42
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 16 publications
8
42
0
Order By: Relevance
“…In this series of 333 patients undergoing surgical repair of acute type A aortic dissection by means of DHCA, spanning a 5-year time period, 136 patients were diagnosed as presurgical mild ARDS, with an incidence of 40.8%. The incidence of presurgical mild ARDS in this series was similar to other series which reported the incidence of 30-45%, [1][2][3][4][5] and this study showed that patients in the mild-ARDS group, compared with the no-ARDS group, had significantly higher plasma levels of inflammatory marker, C-reactive protein, which was consistent with the findings of previous studies. [17][18][19] So, this study again suggested that systemic inflammation played an important role in the occurrence and development of mild ARDS.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In this series of 333 patients undergoing surgical repair of acute type A aortic dissection by means of DHCA, spanning a 5-year time period, 136 patients were diagnosed as presurgical mild ARDS, with an incidence of 40.8%. The incidence of presurgical mild ARDS in this series was similar to other series which reported the incidence of 30-45%, [1][2][3][4][5] and this study showed that patients in the mild-ARDS group, compared with the no-ARDS group, had significantly higher plasma levels of inflammatory marker, C-reactive protein, which was consistent with the findings of previous studies. [17][18][19] So, this study again suggested that systemic inflammation played an important role in the occurrence and development of mild ARDS.…”
Section: Discussionsupporting
confidence: 82%
“…According to published data, [1][2][3][4][5] acute lung injury (or mild ARDS) is one of most common presurgical compli-cations caused by systemic inflammatory response resulted from aortic injury due to acute type A aortic dissection. In this series of 333 patients undergoing surgical repair of acute type A aortic dissection by means of DHCA, spanning a 5-year time period, 136 patients were diagnosed as presurgical mild ARDS, with an incidence of 40.8%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although open heart surgery for treating Stanford A aortic dissection has been a universal option, the patients are still threatened by the lethal perioperative complications such as hemorrhage, hypoxemia, renal dysfunction, cerebral dysfunction and etc. Postoperative hypoxemia is defined as an oxygen fraction (PaO 2 /FiO 2 ) ≤200 mmHg under mechanical ventilation in the first 24 hour after surgery [1]. As a matter of fact, postoperative hypoxemia resembles ARDS (acute respiratory distress syndrome) when oxygen fraction is below 200 mmHg.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 If surgical stress could be minimized by reducing the duration of brain ischemic stress, CPB, and operative procedures, the surgical outcome for AAD could be improved. We describe our newly modifi ed procedure named "less invasive quick replacement" (LIQR) characterized by moderate hypothermic arrest and aggressive rapid rewarming to prevent the complications associated with DHA, extended cerebral protection, CPB, and operative times.…”
Section: Introductionmentioning
confidence: 99%